Five have a wonderful time - Blyton, Enid; Soper, Eileen Alice (Hodder Children's London, 1997)
"The Famous Five are on holiday in horse-drawn caravans - and they've discovered a ruined castle nearby! But the castle isn't empty - the Famous Five have seen a desperate face at the tower window! Whi is hiding in the castle?"--Back cover